The Influence of the Cooperative Model of Bamboo Dance Aided by Puppet Media on Science Learning Outcomes - Septi Fitria Pamungkas Sari; Muhammad Japar; Agrissto Bintang Aji Pradana (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the Bamboo Dance Type Cooperative model with the help of Wayang media on science learning outcomes. The type of research used is experimental research with a one group pretest posttest design with 19 students selected by saturated sampling as the research subjects for fifth grade students of SD Negeri Balekerto. Data collection techniques in the form of test (pretest and posttest). The analysis used is the Wilcoxon test by comparing the posttest and posttest scores. This analysis is used to determine the effect of the cooperative model of the Bamboo Dance type assisted by the Wayang media on science learning outcomes. The results showed that the cooperative model of the Bamboo Dance type assisted by the Wayang media affected the science learning outcomes. This is evidenced by the increase in the average pretest and posttest scores before and after being treated with the Bamboo Dance Cooperative Model with the help of Wayang media. The average pretest score before treatment was 42.05 while the post-test average after being treated was 79.42. The increase in science learning outcomes on the Human Digestive System material can be seen from the results of the Wilcoxon test which shows the probability of a significant value (2-tailed) 0.000 <0.05. This shows a significant change in mastery of concepts after treatment, so it can be concluded that the use of the Bamboo Dance Type Cooperative model with the help of Puppet Media has an effect on science learning outcomes.